2015
DOI: 10.1159/000439063
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience with Insertable Cardiac Monitors to Find Atrial Fibrillation in Cryptogenic Stroke

Abstract: Background: The characteristics of atrial fibrillation (AF) episodes in cryptogenic stroke patients have recently been explored in carefully selected patient populations. However, the incidence of AF among a large, real-world population of patients with an insertable cardiac monitor (ICM) placed for the detection of AF following a cryptogenic stroke has not been investigated. Methods: Patients in the de-identified Medtronic DiscoveryLink™ database who received an ICM (Reveal LINQ™) for the purpose of AF detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 36 publications
3
37
0
4
Order By: Relevance
“…In the CRYSTAL AF study, if monitoring had stopped at 30 days as recommended in the current guidelines, most AF would have been missed, given that the median time from randomization to AF detection was 84 days (interquartile range, 18–265) at 12 months. Furthermore, several studies using insertable cardiac monitors to monitor CS patients have also shown average times to diagnosis longer than 30 days and ranging from 41 to 152 days (Table ) . Future research should characterize the time course for AF detection post‐CS and the progression of AF over time.…”
Section: Clinical and Economic Evidence Gaps For Monitoring Af In Crymentioning
confidence: 99%
“…In the CRYSTAL AF study, if monitoring had stopped at 30 days as recommended in the current guidelines, most AF would have been missed, given that the median time from randomization to AF detection was 84 days (interquartile range, 18–265) at 12 months. Furthermore, several studies using insertable cardiac monitors to monitor CS patients have also shown average times to diagnosis longer than 30 days and ranging from 41 to 152 days (Table ) . Future research should characterize the time course for AF detection post‐CS and the progression of AF over time.…”
Section: Clinical and Economic Evidence Gaps For Monitoring Af In Crymentioning
confidence: 99%
“…7,8 This algorithm has been validated in adult patients to assist in P-wave detection. 9,10 Further research has demonstrated that a sensed R-wave amplitude of at least 0.2 mV is required for arrhythmia detection.…”
Section: Introductionmentioning
confidence: 99%
“…Ziegler et al in their review of the de‐identified Medtronic Discovery Link database also detected AF at a median duration of 112 days in 21% of patients postcryptogenic stroke with better results seen using continuous monitoring over intermittent monitoring . Brachmann et al concluded that the longer the time over which continuous monitoring was performed, the higher the yield of diagnosing AF in the CRYSTAL–AF study . Ziegler reproduced the same results in a real‐world cohort .…”
Section: Discussionmentioning
confidence: 81%